Alpine Marsh Tits Poecile palustris palustris exhibit no clear sexual dimorphism other than in wing length. Issue 1 (2nd January 2018) - Polo Aparisi, Manuel; Schöll, Eva Maria; Hille, Sabine Marlene
ABSTRACT: Sexing Marsh Tits Poecile palustris by wing length has long been general practice in Europe but has recently been under discussion again in Great Britain. Although this debate has concentrated on British populations of the subspecies P.p. dresseri, we contribute in two ways – first by studying a population of the nominate form P.p. palustris in eastern Austria and second by applying a multivariate approach to a series of biometric variables alongside wing length. We measured 13 further biometric parameters that are known to differ between sexes and calculated conditional inference trees to identify the best sex-differentiating variable. With no misclassifications detected, we proved wing length to be the most reliable variable to identify sexes throughout age classes, with males exhibiting wings longer than 64 mm. Lengths of sixth, seventh and eighth primaries and of tail feathers could also be used, but sex was identified less accurately (with 4.8–6.7% misclassifications). Other biometric measurements, like body mass and the lengths of tarsometatarsus, bill and remaining primary feathers, were not suitable for sex differentiation.